2020
DOI: 10.1016/j.vas.2020.100135
|View full text |Cite
|
Sign up to set email alerts
|

The growth of domestic goats and sheep: A meta study with Bertalanffy-Pütter models

Abstract: Highlights We studied 122 mass-at-age data for goats, sheep, and wildlife. We used Bertalanffy-Pütter models to obtain better fitting growth curves. The Brody model had an acceptable fit to 70% of the data. For 39% of data the best-fitting BP-model had a discernable inflection-point. For these models, maximal weight gain per day was 55% higher than natal weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…We nevertheless used the five-parameter BP-model for our research, as initially we were interested in another question: We observed that for about half of the birds the best-fit exponent-pair was close to the diagonal ( Fig 3 ). We had similar observations also for other species [ 29 ]. Was there a biological reason for this?…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We nevertheless used the five-parameter BP-model for our research, as initially we were interested in another question: We observed that for about half of the birds the best-fit exponent-pair was close to the diagonal ( Fig 3 ). We had similar observations also for other species [ 29 ]. Was there a biological reason for this?…”
Section: Discussionsupporting
confidence: 87%
“…m(0) = c > 0. This model was recently recommended in epidemiology [22][23][24] and it was also proposed [25] and applied [26][27][28][29] for studies in animal growth, where the BP-model (1) achieved significant improvements over the logistic model and other simpler three-parameter models with respect to the fit of the data. However, the benefits of its use remained little known and insufficiently evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…For literature data about sheep and goats there was a similar observation about the difficulty to identify sigmoidal growth data (Brunner and Kuhleitner 2020). There the Brody model was outstanding.…”
Section: Discussionmentioning
confidence: 80%
“…The general BP model has been successfully used to describe the growth of chickens (Kuhleitner et al 2019), dinosaurs (Brunner et al 2019), fish (Renner-Martin et al 2018), or goats and sheep (Brunner and Kuhleitner 2020). Here we asked if the BP model could provide additional insight into the growth of cattle, whereby we aimed at recommendations about growth modelling for practitioners: we compared linear and nonlinear models and asked which type of model might be most suitable for modelling the biological growth of cattle.…”
mentioning
confidence: 99%
“…Given the large differences between breed sizes in sheep and goats (ranging from an adult pygmy goat weighing 25-30 kg to adult Tyrolean mountain sheep weighing 100-130 kg), liveweight for all animals was also estimated using the Brody growth curve dependent on sheep or goat breed standards. [14][15][16] The breed and sex of the patient were taken from the clinical records. The breed-specific liveweight of adult animals was taken, where possible, from the book 'The colour atlas of domestic livestock breeds (Farbatlas Nutztierrassen)'.…”
Section: Liveweight Calculationsmentioning
confidence: 99%